Factors Influencing Intention in Implementing an External Whistleblowing System - Maulana, Rifqi; Yvonne Augustine Sudibijo (Technium Social Sciences Journal, 2024)
This studies goals to research and decide the simultaneous and partial affect of Instrumental, Affective, Self-Efficacy, Perceived Controllability, and Independence Commitment on External Whistleblowing Intention with Perceived Organizational Support as a moderating variable. This studies makes use of quantitative research with purposive sampling methods. This research combines internal factors in the form of personality and external factors in the form of the organizational environment as a basis for implementing external whistleblowing, to find out which factors are able to encourage whistleblowers to implement external whistleblowing. This is a primary data originating from questionnaire respondents. The questionnaire was made in electronic form, using Google Form media. Respondent data came from Senior Auditors and Supervisory Auditors of Public Accounting Firms (KAP) in Indonesia, totaling 100 respondents. SmartPLS version 3 was used for analysis. Results indicate that Instrumental variable has a positive effect on External Whistleblowing Intention. Affective has no effect on External Whistleblowing Intention. Self-Efficacy has no effect on External Whistleblowing Intention. Perceived Controllability has no effect on External Whistleblowing Intention. Independence Commitment has no effect on External Whistleblowing Intention. Perceived Controllability does not moderated by Perceived Organizational Support on External Whistleblowing Intention. Affective does not moderated by Perceived Organizational Support on External Whistleblowing Intention. Independence Commitment does not moderated by Perceived Organizational Support on External Whistleblowing Intention. Self-Efficacy does not moderated by Perceived Organizational Support on External Whistleblowing Intention. Instrumental does not moderated by Perceived Organizational Support on External Whistleblowing Intention. This research has limitations. The data was obtained from an instrument based on answers based on the respondents’ perceptions and experiences. Research data can be biased, because if the respondent’s answers are different from their perceptions and experiences of the actual situation, it can reduce the accuracy of the information from this research.